The Role Of The Staff In Improving Work Operations At The Coffee Shop To Increase Guest Satisfaction At Garuda Plaza Medan Hotel - Herti Ginting; Anggi Novika sari (Enrichment : Journal of Management, 2021)
This study aims to determine the waiter's service to guest satisfaction, know the sense of empathy and sympathy of the waiter to the guest's happiness, and know the supervisor's supervision of the waiter's service in the restaurant. This research was conducted on waiters, supervisors, and guests. There are five waitresses in the Coffee Shop, two supervisors, and sampling for guests. The results showed that 65% of waiters did not know about service in increasing guest satisfaction, 57.15% of supervisors did not supervise the work of the waiter in improving operations. working at the Coffee Shop and 65.72% of guests feel less satisfied and comfortable with the services provided by the waitress at the Coffee Shop